POLA PERILAKU KEBERAGAMAAN SISWA SMA NEGERI KABUPATEN MANOKWARI - Abdul Kadir R (Balai Penelitian dan Pengembangan Agama Makassar, 2008)
This research aims to describe religious comprehension, attitude, andbehavior of high school student. This was conducted in SMAN I andSMAN 2 Manokwari, West Papua. Data was collected using questionerto among one hundred students of both high schools, and analyzedusing quantitative method.The result of research showed that religious comprehension, attitude,and behavior of high school student at good level. It means that moststudents of high school have good comprehension, good attitude, andgood behavior. But, this research also showed that few students havebad comprehension, bad attitude, and bad behavior.